Β3 adrenergic receptor as potential therapeutic target in ADPKD. Issue 20 (21st October 2021) - Schena, Giorgia; Carmosino, Monica; Chiurlia, Samantha; Onuchic, Laura; Mastropasqua, Mauro; Maiorano, Eugenio; Schena, Francesco P.; Caplan, Michael J.
Abstract: Autosomal dominant polycystic kidney disease (ADPKD) disrupts renal parenchyma through progressive expansion of fluid‐filled cysts. The only approved pharmacotherapy for ADKPD involves the blockade of the vasopressin type 2 receptor (V2R). V2R is a GPCR expressed by a subset of renal tubular cells and whose activation stimulates cyclic AMP (cAMP) accumulation, which is a major driver of cyst growth. The β3‐adrenergic receptor (β3‐AR) is a GPCR expressed in most segments of the murine nephron, where it modulates cAMP production. Since sympathetic nerve activity, which leads to activation of the β3‐AR, is elevated in patients affected by ADPKD, we hypothesize that β3‐AR might constitute a novel therapeutic target. We find that administration of the selective β3‐AR antagonist SR59230A to an ADPKD mouse model (Pkd1 fl/fl ;Pax8 rtTA ;TetO‐Cre) decreases cAMP levels, producing a significant reduction in kidney/body weight ratio and a partial improvement in kidney function. Furthermore, cystic mice show significantly higher β3‐AR levels than healthy controls, suggesting a correlation between receptor expression and disease development. Finally, β3‐AR is expressed in human renal tissue and localizes to cyst‐lining epithelial cells in patients. Thus, β3‐AR is a potentially interesting target for the development of new treatments for ADPKD. Abstract : The β3‐AR is a GPCR expressed in most segments of the murine nephron, where it modulates cAMP production. We investigate β3‐AR potential as therapeutic target in ADPKD and show that targeted β3‐AR blockade leads to a reduction in kidney/body weight through a decrease in total cAMP renal levels in a mouse model of ADPKD. Furthermore we report evidence of β3‐AR presence in biopsies from healthy and ADPKD patients.